2000
DOI: 10.1007/pl00013421
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive airway disease caused by Moraxella catarrhalis after renal transplantation

Abstract: We report a case of severe acute obstructive airway disease 2 months after renal transplantation in a 16-year-old patient with Biedl-Bardet syndrome who was transplanted for end-stage renal failure secondary to cystic kidney disease. Symptoms of severe obstructive airway disease developed 2 months after transplantation under immunosuppression with prednisone, azathioprine, and tacrolimus. The patient did not develop signs of infection; progressive shortness of breath remained the only symptom for several weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Severe pulmonary complications in children undergoing renal transplantation include pneumonia, e.g., caused by CMV, opportunistic infections (5,6) or fungi (7). A severe obstructive airway disease caused by Moraxella catarrhalis in a renal transplant patient has also been described (8). Morelon et al first reported a sirolimus-induced pneumonitis (9), which was later found to affect nearly 5% of pediatric renal transplant patients (10).…”
Section: Discussionmentioning
confidence: 99%
“…Severe pulmonary complications in children undergoing renal transplantation include pneumonia, e.g., caused by CMV, opportunistic infections (5,6) or fungi (7). A severe obstructive airway disease caused by Moraxella catarrhalis in a renal transplant patient has also been described (8). Morelon et al first reported a sirolimus-induced pneumonitis (9), which was later found to affect nearly 5% of pediatric renal transplant patients (10).…”
Section: Discussionmentioning
confidence: 99%